STUDI KANDUNGAN LOGAM BERAT CADMIUM (Cd) PADA KERANG HIJAU (Mytilus viridis) YANG DIJUAL DI PASARTRADISIONAL PABEAN KOTA SURABAYA - Ita Noryani; Koerniasari .; AT. Diana Nerawati (GEMA LINGKUNGAN KESEHATAN, 2013)
Green mussels ( Perna viridis/Mytilus viridis) live in tropical seas such as those inIndonesia. Sea is one of waters that receive the negative impact of pollutant wastes producedby human activities. Heavy metals are among those pollutants mostly found in waters as theconsequence of industrial waste and domestic waste contamination. Cadmium has the highestenzyme activity among those other heavy metals, so that the existence of cadmium in greenmussels may endanger one's health since it can cause a damage to urinary, respiration,Circulation, and reproduction systems.The aim of this study is to learn about the cadmium content in green mussels fromKenjeran, Sidoarjo and Madura sold at Pabean Market of Surabaya. The method employed inthis study is descriptive method based on laboratory test result. The sampling is done bymeans of purposive sampling and there are 6 samples taken from 6 green mussels sellers.It can be concluded from this study that green mussels from 3 regions namelySidoarjo, Kenjeran and Madura sold at Pabean Market positively show pink color after beingqualitatively tested with color test in the laboratory, while quantitatively it is proven thatcadmium content in those green mussels is above the floating limit score of 0,2 ppmestablished by SNI under No. 01-2896-1998. The cadmium content in green mussels fromKenjeran is of 0,369 ppm and 0,348 ppm, Sidoarjo is of 0,258 ppm and 0,267 ppm, andMadura is of 0,212 ppm and 0,217 ppm.It is suggested that people must be very careful while consuming those green musselsfrom Kenjeran, Madura or Sidoarjo which content of cadmium is over the permitted limitestablished by SNI since it may cause health problem and body damage. One way to reducethe risk of cadmium danger is to soak the mussels in an acid solution of cooking star fruit andlime before cooking them